The Challenges of Pre-Service Teachers in the New Normal Set up of Field Study Amidst COVID-19 Pandemic - Trixie B Baldomar; Geri Mae G Cunanan; Bryan Jacob G Marquez; Freddie P Ortiguero Jr; Michelle C Padre; Hannah L Rey (Advanced Journal of STEM Education, 2023)
The pandemic had a huge impact on many things and situations, particularly the new normal. The researchersdecided that a field study of pre-service teachers is one of them because no one has ever taken the course under thenew COVID-19 setup. The researchers aim to inform their readers about how the COVID-19 pandemic challenge willaffect every pre-service teacher in the new set-up of education through online learning. Purposive homogenoussampling was used to choose 12 students from Rizal Technological University-Boni and Pasig Campuses. Researcherschose typical students, non-workers, and university scholars as participants. Age, gender, and geography vary amongparticipants. Researchers used interviews supported by an interview script to gather replies. Pandemic-relatedpreparations have been taken. Thematic analysis is used to understand pre-service teachers' challenges in the newfield study setup. Pre-service teachers face challenges in this setting, according to the research most are strugglingbecause of the rapid move from traditional classes to the new typical format, causing unpreparedness and lack ofexpertise when they face more complex situations. In addition, slow internet and a lack of resources make it difficultto attend classes and meet prerequisites. Some have many restrictions, especially on classroom monitoring becauseof the pandemic. The findings imply that the study's premise is significant and relevant in today's environment,especially for individuals pursuing an education degree and becoming pre-service teachers. Pre-service teachers facenew obstacles in the new normal.